Low temperature ensures FeS2 cathode a superior cycling stability in Li7P3S11-based all-solid-state lithium batteries - Wang, Ru; Wu, Zhongkai; Yu, Chuang; Wei, Chaochao; Peng, Linfeng; Wang, Liping; Cheng, Shijie; Xie, Jia (Frontiers in Energy Research, 2023)
All-solid-state lithium sulfide batteries exhibit great potential as next-generation energy storage devices due to their low cost and high energy density. However, the poor conductivity of the solid electrolytes and the low electronic conductivity of sulfur limit their development. In this work, the highly conductive Li7P3S11 glass-ceramic solid electrolyte with room temperature conductivity of 1.27 mS cm-1 is synthesized and combined with the FeS2 cathode and Li-In anode to fabricate FeS2/Li7P3S11/Li-In all-solid-state Li-S battery. The assembled battery delivers high initial discharge capacities of 620.8, 866.4 mAh g-1, and 364.8 mAh g-1 at 0.1C under room temperature, 60 oC and 0 oC, respectively. It shows a discharge capacity of 284.8 mAh g-1 with a capacity retention of 52.4% after 80 cycles at room temperature. When the operating temperature rises to 60 oC, this battery suffers a fast decay of capacity in 40 cycles. In contrast, this battery sustains a high discharge capacity of 256.6 mAh g-1 with a capacity retention of 87.9% after 100 cycles under 0 oC. The smaller volume expansion of the battery at 0 oC ensures excellent solid/solid interface contacts, resulting in superior electrochemical performances at this operating temperature. EIS and in-situ pressure characterizations further verify that the differences in electrochemical performances are associated with the volume variations caused by the temperature effects. This work provides a guideline for designing all-solid-state Li-S which is workable in a wide temperature range.